PEMBATASAN HAK MENGUASAI NEGARA OLEH MASYARAKAT ADAT DALAM PENGELOLAAN SUMBER DAYA AIR - Diah Pawestri Maharani (Arena Hukum, 2016)
AbstractWater is a basic requirement of all living creatures on earth. One one hand, the available of water in nature which potentially can be exploited by human tend to quality decline. On the other hand, the need of water always increase over time, not only because of the increace of human population, but also because of the intensity of the variation needs of water as a commercial comodities. Hence the imbalance between supply and demand of water raises conflict. This problem do not only occur among communities, or between societies and investors, but also occur between Indigeneous Communities with the State. In this paper the authors would like to highlight about the authority of the State in managing water resources included in determining policies. State authority is rooted in the constitutional mandate of the 1945 Constitution which states: "The Act of 1945, in particular article 33, paragraph (3), which reads:" Earth and water, and natural resources contained itside is controlled by the State and used for the greatest prosperity of the people ". This article emerges basic concepts of the state rights of water resources. However, it is possible for the political law made by the State to deprive customary rights and fundamental rights of indigenous people who should be able to enjoy the water resources. In another regulation, namely Law No. 6 of 2014 about Desa (village), Article 103 letter b regulates the authorities of the Village People based on the origin of the rights owned by the Village People, including the setting and maintenance of their customary or indigenous territories. In this paper the author tries to analyze the State authority limitation when confronted with the authority of indigenous peoples relate to the same object, that is water in indigenous territories in Indonesia. The Author will use normative method and conceptual analysis.AbstrakAir merupakan kebutuhan pokok seluruh makhluk hidup di dunia. Di satu sisi, ketersediaan air yang secara potensial dapat dimanfaatkan manusia, secara kualitas cenderung menurun. Sedangkan kebutuhan manusia akan air sebagai komoditas ekonomi selalu mengalami peningkatan dari waktu ke waktu. Ketidakseimbangan antara ketersediaan dan kebutuhan air inilah kemudian rentan menimbulkan konflik. Konflik sumber daya air tidak hanya terjadi dalam antara masyarakat dengan masyarakat, masyarakat dengan Investor, namun juga antara Masyarakat dengan Negara. Dalam tulisan ini penulis ingin menyoroti tentang kewenangan Negara dalam melakukan pengelolaan sumber daya air termasuk dalam hal menentukan kebijakan-kebijakannya. Kewenangan Negara ini bersumber pada amanat konstitusi UUD 1945 khususnya pasal 33 ayat (3) yang berbunyi: â€œBumi dan air, dan kekayaan alam yang terkandung didalamnya dikuasai oleh Negara dan dipergunakan untuk sebesar-besar kemakmuran rakyatâ€. Pasal tersebut melahirkan konsep dasar Hak Menguasai sumber daya air oleh Negara. Tetapi, sangat dimungkinkan politik hukum yang ditetapkan oleh Pemerintah justru merampas hak ulayat dan hak-hak dasar masyarakat adat yang seyogianya dapat menikmati sumber daya air tersebut. Dalam regulasi lain yaitu UU Nomor 6 Tahun 2014 tentang Desa, Pasal 103 huruf b mengatur kewenangan Desa Adat berdasarkan hak asal-usul yang dimiliki oleh Desa Adat, termasuk pengaturan dan pengurusan ulayat atau wilayah adat mereka. Dalam tulisan ini penulis akan menguraikan pembatasan kewenangan Negara jika dihadapkan pada kewenangan masyarakat adat atas satu objek yang sama yaitu air dalam wilayah adat di Indonesia. Tulisan ini disusun dengan menggunakan metode penulisan yuridis normatif dengan pendekatan konseptual dan analisis.